Study The Improvement Myco-manufacturing of Crud Bikaverin by Fusarium oxysporum with Evaluation The Antimicrobial Effectiveness - Ali J Al-Sa'ady; J Al-Obaidi, Mohammed; Ahmad Y Hanoon (University of Thi-Qar Journal of Science, 2023)
Bikaverin is a reddish pigment produced by a variety of fungal species, the majority of which belong to the Fusarium genus. This pigment has antibiotic activities against protozoa, bacteria, and fungus. This study investigated the toxicity of Bikaverin to some microbs, production, and characterization of the pigment from the fungus Fusarium oxysporum. The yield of total bikaverin in F. oxysporum shake flask culture was improved by optimizing cultivation variables such as complex medium, carbon supply, nitrogen source, temperature, medium pH, and incubation period. After 10 days and at 28°C in Potato dextrose broth [PDB] supplemented with 2% glucose, 2% corn step liquor, and a pH of 5.5, the maximum production of complete bikaverin was discovered. The isolates of more sensitive bacteria to bikaverin were Staphylococcus aureus and S. typhi, with inhibition zones 24 and 23 mm respectively, at a concentration of 75 μg/mL. The isolates more sensitive bacteria to bikaverin were  E. faecalis,  E. coli and P. aeruginosa while fungi was C. albicans with inhibition zones of 18, 22, 20 and 13 mm, respectively, at a concentration of 75 μg/mL. The results showed that the toxic antimicrobial activity of bikaverin was clear against fungi and bacteria.